Bibliometric analysis with special reference to authorship patterns and collaborative research in the libri: international journal of libraries and information services - Daud, Khan (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2017)
The ultimate purpose of the present study is to explore the bibliometric analysis of the LIBRI: International Journal of Libraries and Information Services journal during the period of 2011-2015. The analysis covers sundry features of the journal such as its yearly output of articles, subject distributions, geographical distributions of authors, authorship patterns, relative growth rate and double time of publication. The result concludes that 140 research articles were pubished in the LIBRI journal during the stipulated span i.e. 2011-2015, in which 63 (45%) articles were written by a single author whereas 77 (55%) articles were multi-authored. In the study, the average degree of author collaboration was 0.55 and it ranged from 0.57 to 0.58. Keywords: LIBRI. Bibliometric analysis. Authorship pattern. Author productivity. Degree of collaboration. Link: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/5821